Interactive Effects of Fertilizer Types and Shading Levels on ‎Growth, Yield, and Piperine Content of Piper Retrofractum Under ‎Tropical Agroecosystems - Pramono Hadi; Riski Rahma Noviana; Suwardi; Agung Mugi Widodo (ISEJ : Indonesian Science Education Journal, 2026)
Piper retrofractum (Javanese long pepper) is an economically important medicinal plant valued for its piperine content. However, its productivity and quality remain inconsistent under tropical agroecosystems due to suboptimal nutrient management and light conditions. This study aimed to evaluate the interactive effects of fertilizer types and shading levels on growth, yield, and piperine content, as well as to determine the relationships among these variables. A factorial completely randomized design was employed with two factors: fertilizer types (NPK, biofertilizer, local microbial liquid organic fertilizer, and a combination of NPK and biofertilizer) and shading levels (0%, 40%, and 60%), resulting in 12 treatment combinations with three replications. The observed parameters included number of productive branches, dry fruit weight per plant, and piperine content. Data were analyzed using ANOVA, followed by DMRT at 5%, and strengthened with Pearson correlation and multiple regression analyses. The results showed that the combination of NPK and biofertilizer under no shading significantly produced the highest values for all parameters. Productive branches exhibited a very strong positive correlation with dry fruit weight (r = 0.88**) and moderate correlation with piperine content (r = 0.61*), while dry fruit weight showed a strong correlation with piperine content (r = 0.69**). The regression model (R² = 0.88) indicated that both productive branches and dry fruit weight significantly contributed to piperine content, with dry fruit weight having a greater influence. These findings highlight that optimizing fertilization strategies and light conditions can simultaneously enhance yield and bioactive compound accumulation in P. retrofractum under tropical conditions.